Diagnostic Accuracy and Cost‐Effectiveness of a Pocket‐Sized Transthoracic Echocardiographic Imaging Device. Issue 10 (24th July 2013) - Kitada, Ryoko; Fukuda, Shota; Watanabe, Hiroyuki; Oe, Hiroki; Abe, Yukio; Yoshiyama, Minoru; Song, Jong‐Min; Sitges, Marta; Shiota, Takahiro; Ito, Hiroshi; Yoshikawa, Junichi
Abstract Background The recently introduced pocket‐sized portable transthoracic echocardiography (pTTE) is accurate for measurement of cardiac chamber size and function as well as for assessment of valvular regurgitation. This study aimed to compare the diagnostic accuracy of the pocket‐sized pTTE with the standard TTE (sTTE) and assess its cost‐effectiveness. Hypothesis The use of pocket‐sized pTTE, as an initial screening tool, may be feasible, accurate and cost‐effective in the diagnostic strategy of cardiac abnormalities. Methods The study subjects were 200 patients scheduled for sTTE and an electrocardiogram (ECG). Each patient underwent pTTE examination with the Vscan (GE Medical Systems, Milwaukee, WI) immediately after sTTE. The findings of pTTE and the ECG were compared with the results of sTTE. Cost‐effectiveness was calculated. Results There was a strong agreement in the detection of abnormal findings between pTTE and sTTE (agreement = 90%), whereas the agreement between the ECG and sTTE was 65%. When pTTE or the ECG was used as an initial screening tool prior to sTTE, similar cost reduction was obtained (approximately 30%) by reducing the number of referrals for sTTE. However, the negative predictive value of a diagnostic strategy with pTTE (92%) was superior to that with an ECG (67%). Conclusions This study demonstrates that the pocket‐sized pTTE provides accurate detection of cardiac structural and functional abnormalities beyond the ECG. In addition, the use of pTTE as an initial screening tool prior to sTTE is cost‐effective, suggesting that the pocket‐sized pTTE is poised to alter the current diagnostic strategy in clinical practice.